Management of acute type A aortic dissection during COVID‐19 outbreak: Experience from Anzhen. Issue 5 (16th September 2020) - Zhang, Chen‐Han; Ma, Wei‐Guo; Zhong, Yong‐Liang; Ge, Yi‐Peng; Li, Cheng‐Nan; Qiao, Zhi‐Yu; Liu, Yong‐Min; Zhu, Jun‐Ming; Sun, Li‐Zhong
Abstract: Objectives: We seek to report our management protocol and early outcomes of acute type A aortic dissection (ATAAD) repair during the early phase of coronavirus disease 2019 (COVID‐19). Methods: From January 23 to April 30, 2020, we performed ATAAD repair for 33 patients, including three with pregnancy‐related TAADs. Confirmation of COVID‐19 depended on the results of two nucleic acid tests and pulmonary computed tomography scan. Based on testing results and hemodynamic stability, patients were triaged to an isolated intensive care unit or negative pressure operating room for emergency surgery. Results: Mean age 50.2 ± 13.3 years and 20 were male (60.1%) and 8 patients were febrile (>37.3°C; 24.2%) and 17 were lymphopenic (51.5%). No patient was excluded from COVID‐19 infection preoperatively. Extensive aortic repair with total arch replacement (TAR) was performed in 24 (72.7%), and limited proximal repair in 9 patients (27.3%). Cardiopulmonary bypass and cross‐clamp times averaged 177 ± 34 and 88 ± 20 min for TAR, and 150 ± 30 and 83 ± 18 min for hemiarch, respectively. The mean operation time was 410 ± 68.3 min. Operative mortality was 6.1% (2/33). Complications included reintubation in four (12.1%), acute kidney failure in two (6.1%), and cerebral infarction in one (3.0%). No paraplegia nor re‐exploration for bleeding occurred. COVID‐19 was excluded in 100% eventually. No nosocomial infection occurred. Nor did any patient/surgical staff develop fever or test positive during the study period. Conclusions: The results of this study show that our management protocol based on testing results and hemodynamic stability in patients with ATAAD during the COVID‐19 pandemic was effective and achieved favorable early surgical outcomes.